Linguagem corporal e educação física - Santos, Rochelle Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Communication has long been a relevant and powerful factor in many fields of study. The interaction with the world and the fact that they are observable, the differences and similarities in several spheres, makes it interesting in the daily life of several professionals. For physical education it can be another tool of study, a means of understanding some bodily manifestations, as well as a specific language form at certain times. When observing an individual, some aspects stand out and others go unnoticed. These aspects vary according to several situations that somehow become remarkable to the behavior of the same. The world that is known has different societies and forms of language, and it is possible to learn a lot by seeking to observe, analyze and understand these languages. Try to understand a little of the mystery that each person takes within themselves, or just learn to be in solidarity the forms of bodily manifestation as behavior of people that will always be a riddle to us, and even our own mysteries. The proposal of this study is a review of the literature in the areas mentioned, a summary of general knowledge in the field of communication and information, as well as the gathering of some specific aspects in establishing interdisciplinary relations between different languages with human movement in different fields. can become an ally in future studies and a further guide to learning physical education

A comunicação há tempos é um fator relevante e poderoso em diversos campos de estudo. A interação com o mundo e o fato de serem observáveis, as diferenças e semelhanças em diversos âmbitos, à torna interessante no cotidiano de diversos profissionais. Para a educação física pode ser mais uma ferramenta de estudo, um meio de entender algumas manifestações corporais, assim como forma de linguagem específica a certas ocasiões. Ao observar um indivíduo, alguns aspectos se destacam e outros passam despercebidos. Tais aspectos variam de acordo com diversas situações que de alguma forma se façam notáveis ao comportamento do mesmo. O mundo que se conhece possui diferentes sociedades e nelas, formas de linguagem, e é possível aprender muito ao buscar observar, analisar e compreender essas linguagens. Tentar compreender um pouco da incógnita que cada pessoa leva dentro de si, ou apenas aprender a ser solidário as formas de manifestação corporal como comportamento de pessoas que sempre serão um enigma para nós, e até mesmo nossos próprios mistérios. A proposta desse estudo é uma revisão de literatura nas áreas citadas, reunião de conhecimento geral resumido no campo da comunicação e informação, assim como a reunião de alguns aspectos específicos ao estabelecer relações interdisciplinares entre diferentes linguagens com o movimento humano em diferentes campos, o que pode vir a ser um aliado nos estudos futuros e mais um guia para a aprendizagem da educação física
Keywords: Linguagem corporal; Educação fisica; Comunicação; Comunicação não-verbal